Modeling and simulation of an active quarter-car suspension system using a synergetic controller - Dao Trong Dung; Trong Nghia Le; Alexandr D. Lukyanov; Nguyen Xuan Chiem (Institute of Advanced Engineering and Science, 2026)
This paper presents the modeling and simulation of an active quarter-car suspension system (AQCSS) designed to enhance operational performance and ride comfort across various road conditions. First, a dynamic quarter-car model was developed, incorporating all the components of AQCSS and road-induced stimuli, based on the Euler–Lagrange method. Subsequently, a synergetic controller is designed by selecting a manifold that meets the system’s technical requirements. The proposed controller ensures a balance between ride comfort and road-holding performance by leveraging this manifold design. This control framework enables flexible adjustment of the damping force in real time according to the system states and external excitations. The stability of the closed-loop system is rigorously established through Lyapunov analysis. Numerical simulations are carried out in MATLAB to assess the proposed control law by benchmarking it against a passive suspension configuration and a sliding mode control approach, thereby demonstrating its effectiveness.